The game of Love and Death - Brockenbrough, Martha (New York, NY Arthur A. Levine Books, an imprint of Scholastic Inc, 2015)
In Seattle in 1937 two seventeen-year-olds, Henry, who is white, and Flora, who is African-American, become the unwitting pawns in a game played by two immortal figures, Love and Death, where they must choose each other at the end, or one of them will die
1
Keywords: African American teenage girls -- Washington (State) -- Seattle -- Juvenile fiction; African Americans -- Fiction; Death -- Fiction; Love -- Fiction; Man-woman relationships -- Juvenile fiction; Race relations -- Fiction; Race relations -- Juvenile fiction; Teenage boys -- Washington (State) -- Seattle -- Juvenile fiction; Seattle (Wash.) -- History -- 20th century -- Fiction; Seattle (Wash.) -- History -- 20th century -- Juvenile fiction